2017
DOI: 10.1128/jvi.02417-16
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus 1 Ubiquitin-Specific Protease UL36 Abrogates NF-κB Activation in DNA Sensing Signal Pathway

Abstract: The DNA sensing pathway triggers innate immune responses against DNA virus infection, and NF-B signaling plays a critical role in establishing innate immunity. We report here that the herpes simplex virus 1 (HSV-1) ubiquitinspecific protease (UL36USP), which is a deubiquitinase (DUB), antagonizes NF-B activation, depending on its DUB activity. In this study, ectopically expressed UL36USP blocked promoter activation of beta interferon (IFN-␤) and NF-B induced by cyclic GMP-AMP synthase (cGAS) and stimulator of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 59 publications
2
94
0
Order By: Relevance
“…In a different study regarding the function of UL36USP, it was found that UL36USP inhibits cGAS and STING dependent IFN-β production [49]. NF-κB activation from overexpressing STING, TBK1, IKKα and IKKβ was also inhibited, but not from overexpressing p65 [49]. In this study, human foreskin fibroblast (HFF) cells were infected with either HSV-1 or HSV-1 C40A mutant and stimulated with IFN stimulatory DNA [49].…”
Section: Ul36uspmentioning
confidence: 87%
See 2 more Smart Citations
“…In a different study regarding the function of UL36USP, it was found that UL36USP inhibits cGAS and STING dependent IFN-β production [49]. NF-κB activation from overexpressing STING, TBK1, IKKα and IKKβ was also inhibited, but not from overexpressing p65 [49]. In this study, human foreskin fibroblast (HFF) cells were infected with either HSV-1 or HSV-1 C40A mutant and stimulated with IFN stimulatory DNA [49].…”
Section: Ul36uspmentioning
confidence: 87%
“…NF-κB activation from overexpressing STING, TBK1, IKKα and IKKβ was also inhibited, but not from overexpressing p65 [49]. In this study, human foreskin fibroblast (HFF) cells were infected with either HSV-1 or HSV-1 C40A mutant and stimulated with IFN stimulatory DNA [49]. As a result, the level of endogenous IκBα in HFF cells with mutant HSV-1 significantly decreased compared to HFF cells with WT HSV-1, supporting that UL36USP decreases the degradation of IκBα in a DUB activity-dependent manner [49].…”
Section: Ul36uspmentioning
confidence: 92%
See 1 more Smart Citation
“…In order to promote infection and replication in host cells, while evading the immune response, many human pathogenic viruses have evolved the ability to hijack and manipulate the UPS (Luo, 2016). For example, the Ub-specific protease of the herpes simplex virus 1 antagonizes NF-κB activation, whereas the E6 oncoprotein of the human papillomavirus recruits host E3 ligases to promote Ub-dependent degradation of p53 and consequent carcinogenesis (Hoppe-Seyler, Bossler, Braun, Herrmann, & Hoppe-Seyler, 2018;Ye, Su, Xu, & Zheng, 2017). We developed highly selective and potent UbVs targeting the DUBs of the Middle East respiratory syndrome coronavirus (MERS-CoV) and the Crimean-Congo hemorrhagic fever virus (CCHFV), two emergent and globally important viruses (W. Zhang, Bailey-Elkin, et al, 2017).…”
Section: Ubv Inhibitors Of Deubiquitinasesmentioning
confidence: 99%
“…Through a variety of mechanisms, several DNA viruses such as adenovirus, herpes simplex virus (HSV)-1, and human papilloma virus (HPV) have been shown to induce or actively inhibit a STING-dependent type I IFN response (Anghelina et al, 2016; Ishikawa et al, 2009; Lam and Falck-Pedersen, 2014; Lam et al, 2014; Liang et al, 2015; Sunthamala et al, 2014). For example, over a dozen proteins of HSV-1 have been found to actively suppress cytosolic-DNA recognition by the cGAS/STING pathway (Christensen et al, 2016; Horan et al, 2013; Ishikawa et al, 2009; Kalamvoki and Roizman, 2014; Su and Zheng, 2017; Xu et al, 2017; Ye et al, 2017; Zhang et al, 2016; Zheng, 2018). Similarly, the E2 proteins of HPV16 inhibit the transcription of different ISGs by targeting STING (Sunthamala et al, 2014).…”
Section: Intracellular Recognition Of Dnamentioning
confidence: 99%